MicroRNAs (miRNAs) AS REGULATORS OF GENE EXPRESSION AND THEIR CLINICAL IMPORTANCE - Ovando Ricárdez, José Antonio; Domínguez Méndez, Viviana Beatriz; López García, María Isabel; Sacramento Barranco, María Lizbeth; Gonzalez Castro, Thelma Beatriz; Hernández Díaz, Yazmíin; Tovilla Zárate, Carlos Alfonso; Juárez Rojop, Isela Esther; López Narváez, María Lilia (Kuxulkab', 2022)
miRNAs are small non-coding endogenous RNAs that regulate gene expression and are involved in the development of various diseases; therefore, they are of therapeutic relevance. The objective of this work is to make known in a general way the role that miRNAs play in the development of diseases and their application as biomarkers. To do this, an observational study was carried out by searching the scientific literature using the PubMed database. The synthesis of the evidence shows us that the processes regulated by miRNAs and the identification of target genes in the development of diseases is a very valuable and exciting strategy that may eventually lead to the development of new treatment approaches.
Keywords: Noncoding RNA; Genetic regulation; Biomarkers